1997
DOI: 10.1007/s002130050318
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sleep EEG microstructure in subchronic paroxetine treatment of healthy subjects

Abstract: Paroxetine is a selective and potent serotonin reuptake inhibitor and its efficacy for the treatment of depression has been proven. Under acute and subchronical treatment regimens, disturbances of the regular sleep pattern are a reported side effect of the drug. The present study was therefore performed to investigate the impact of subchronic treatment with the selective serotonin reuptake inhibitor paroxetine on the microstructure of the sleep EEG. The study especially addressed the question of subchronic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Treatment with citalopram resulted in suppression of spectral power in the 8-9 Hz range. In these studies, no influence of SSRIs on delta power was observed (Röschke et al, 1997;Murck et al, 2003). 5-HT antagonists at presynaptic serotonergic 5-HT1A autoreceptors enhance serotonin release by suppression of the inhibitory effect of 5-HT1A autoreceptors on raphe nuclei neurons (Sharp et al, 1989).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Treatment with citalopram resulted in suppression of spectral power in the 8-9 Hz range. In these studies, no influence of SSRIs on delta power was observed (Röschke et al, 1997;Murck et al, 2003). 5-HT antagonists at presynaptic serotonergic 5-HT1A autoreceptors enhance serotonin release by suppression of the inhibitory effect of 5-HT1A autoreceptors on raphe nuclei neurons (Sharp et al, 1989).…”
Section: Discussionmentioning
confidence: 84%
“…No alterations of the spectral composition of sleep EEG were found during subchronic treatment with paroxetine in healthy subjects (Röschke et al, 1997). Another study in depressed male therapy responders showed a decline of power in the higher frequency sigma range during treatment with paroxetine as well as tianeptine, which enhances serotonin reuptake (Murck et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Specific spectral EEG effects of antidepressants have been reported by several authors (Tarn et al 1993;Saletu and Grünberger 1985;Patat et al 1998;Fischer et al 1986;Yamadera et al 1987;Saletu et al 1991;Röschke et al 1997); furthermore, there is evidence for a link between sleep regulation and depression, with sleep homeostasis being routinely characterized by spectral EEG parameters (Borbély et al 1988;Achermann et al 1993).…”
mentioning
confidence: 88%
“…In case of the spectrum analysis, we do not expect to easily achieve further significant improvements, because much effort in this respect already has been made in many previous studies [25,26]. Other studies have shown that the delta/beta ratio provides the most information about the alterations of the sleep structure [27].…”
Section: Discussionmentioning
confidence: 99%